Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Konsumen pada Kedai Kopi Janji Jiwa - Setiawan, Ainur Rahim; Wahyuni, Aria Dian Tri; Selan, Sarlota; Solikhin, Muhammad (Manajemen & Bisnis Jurnal, 2026)
The present study aims to empirically examine the effect of service quality and pricing on consumer satisfaction at Kedai Kopi Janji Jiwa in Malang. Employing a quantitative approach with a correlational design, this research involved 100 respondents selected through purposive sampling. The primary data were collected using structured questionnaires and subsequently analyzed using multiple linear regression. The empirical results demonstrate that service quality partially exerts a positive and significant impact on consumer satisfaction (t-value = 5.651). Similarly, price positively and significantly influences consumer satisfaction (t-value = 9.462). The simultaneous test reveals that both variables collectively affect consumer satisfaction with an F-value of 649.729. The coefficient of determination (R-square) indicates that 93.1% of the variance in consumer satisfaction is explained by service quality and price, leaving 6.9% to other unexamined factors. These findings suggest that maintaining service consistency and proportional pricing are crucial for sustaining customer satisfaction.